Comparative Study of Traditional and Contemporary Arabic Teaching Materials - Mukhlis Rahman, Muh.; Abdul Hamzah, Andi (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to comparatively examine the characteristics, approaches, and effectiveness of traditional and contemporary Arabic teaching materials in learning. Traditional teaching materials generally focus on classical texts, grammatical-translation approaches, and the use of the yellow book, while contemporary teaching materials tend to be interactive, technology-based, and prioritize a communicative approach. This study uses a descriptive qualitative method with data collection techniques in document studies, interviews with Arabic language educators, and classroom observation in several formal and non-formal educational institutions. The study results show that traditional teaching materials have advantages in preserving classical scientific values and strengthening language structure but are less responsive to modern learning needs. On the other hand, contemporary teaching materials are more adaptive to the times and students' communicative needs but often lack depth in terms of nahwu and Sharaf rules. This study recommends an integrative approach between the two types of teaching materials to create more effective, contextual and balanced Arabic learning.